2012
DOI: 10.1038/nphoton.2012.312
|View full text |Cite
|
Sign up to set email alerts
|

Bell's measure in classical optical coherence

Abstract: The statistical description of optical fields in classical coherence theory is the foundation for many applications in metrology, microscopy, lithography and astronomy. Partial coherence is commonly attributed to underlying fluctuations originating at the source or arising upon passage through a random medium. A less acknowledged source of uncertainty (partial coherence) stems from the act of ignoring a degree of freedom of a beam when observing another degree of freedom coupled to (or classically entangled wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
213
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 234 publications
(226 citation statements)
references
References 35 publications
3
213
0
2
Order By: Relevance
“…Indeed, axially self-similar propagation becomes a generic feature of beams incorporating these correlations in their ST-spectrum. This work can thus be viewed as a generalization of burgeoning working on so-called 'classical entanglement' [48][49][50] to continuous DoFs of the optical field. Previous demonstrations of classical entanglement have been confined to date to discretized DoFs such as polarization and individual spatial or temporal modes.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, axially self-similar propagation becomes a generic feature of beams incorporating these correlations in their ST-spectrum. This work can thus be viewed as a generalization of burgeoning working on so-called 'classical entanglement' [48][49][50] to continuous DoFs of the optical field. Previous demonstrations of classical entanglement have been confined to date to discretized DoFs such as polarization and individual spatial or temporal modes.…”
Section: Resultsmentioning
confidence: 99%
“…This measure has been experimentally examined by Kagalwala et al [24]. One fundamental problem of their formulation is that it varies under global unitary transformations.…”
mentioning
confidence: 99%
“…This analogy between polarization and purity has been discussed by some authors [6]. Some authors have suggested the use of Bell's measure, commonly used in tests of quantum non-locality, to quantify classical optical coherence (polarization) [7]. Others have suggested a particular measure of polarization in higher dimensions [8].…”
Section: Introductionmentioning
confidence: 99%